Analyzing gamma irradiated Spectrolite in relation to the photo-transfer TL and OSL effects - Patrícia de Lara Antonio; Linda Viola Ehlin Caldas (Brazilian Journal of Radiation Sciences, 2025)
Thermoluminescence (TL) and optically stimulated luminescence (OSL) are two techniques based in the luminescence phenomenon. They can be applied to study the response of materials which present the property of emitting light after the steps of irradiation and subsequent stimulus, that can be thermal (in the case of TL) or optical (OSL). These materials may also be capable of exhibiting phototransfer effect in their response, and this characteristic can be observed through the TL photo-transfer (PTTL) and OSL photo-transfer (PTOSL). The purpose of this work was to verify the presence of the PTTL and PTOSL responses on the Spectrolite material, after irradiation with gamma source (60Co) and illumination with LEDs (wavelengths in the UV region), for application in gamma radiation dosimetry. For this, the signal of Spectrolite samples was studied in relation to their TL/PTTL and OSL/PTOSL responses by means of three steps: 1) irradiation and measurement of TL and OSL responses; 2) irradiation, post-irradiation thermal treatment (PITT) and measurement of TL and OSL signals; and 3) irradiation, PITT, illumination with LEDs and measurement of PTTL and PTOSL signals. The results obtained showed the presence of photo-transfer effect in the PTTL response, but not in the PTOSL response; this fact demonstrates the need for further studies to verify the PTTL and PTOSL responses, with variations in the wavelength of light and the illumination time. For application of this material in gamma radiation dosimetry, these other studies are needed.